Analisis Model Pengambilan Keputusan Dalam Implementasi Kebijakan Ganjil Genap Di Jakarta Guna Mengurangi Kemacetan Dilihat Dari Teori Rasionalitas - Hanifa Putri Ambarini; Adinda Sukma Ayu; Adam Jamal (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
DKI Jakarta faces significant traffic congestion due to the increasing population and number of motor vehicles. This research uses a qualitative approach through literature review to identify the factors causing congestion and to formulate effective solutions.The findings reveal that congestion is caused by high private vehicle usage, low use of public transportation, and limited road space. The proposed solutions in this study include improving public transportation infrastructure, implementing an odd-even traffic policy, and enforcing a 3 in 1 rule for cars. The analysis results show that implementing the odd-even policy is the most effective solution to reduce congestion. This policy has proven to reduce the volume of vehicles on the road and encourages the public to switch to public transport, significantly reducing exhaust emissions, improving air quality, increases the efficiency of road space usage, and lowers the traffic accident rate. The success of this solution requires active support and participation from the public. Therefore, the government needs to continuously involve the public in the decision-making process and provide adequate education about the impact and urgency of congestion issues. Collaboration between the government and the public is crucial to creating effective solutions to address congestion and enhance sustainable mobility in Jakarta.